ANALISA RENCANA INVESTASI PADA PENGEMBANGAN LINTASAN PRODUKSI NEW MODEL CRANK CASE TIPE SPORT DI PT XYZ - Komarudin Komarudin; Purwi Timur Iswari; Ryani Dhyan Parashakti (Bina Teknika, 2020)
XYZ Company is currently planning the production machining line for crank case new model sports type of 2200 units / day. There are two alternative investment plan that is manual and automation to get the best alternative in terms of finance .Analysis tool used is the Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PBP) as the basis for determining which alternative is chosen. Sensitivity analysis is used to determine which is the most sensitive variable to the NPV .Both alternatives feasible to be realized, but the automation system was chosen because of the analysis results is greater than the value of the manual system with an IRR of 57.52% (IRR > MARR), which MARR 7.88% and a NPV of USD 299 002 634 271 (NPV > 0), and payback of 1 years for 0,27 month, which is faster than the economic life of the machine that 8 years. Total interest rate is the most sensitive factor in changing the NPV